2014
DOI: 10.1074/jbc.m114.565333
|View full text |Cite
|
Sign up to set email alerts
|

Altered Thiol Chemistry in Human Amyotrophic Lateral Sclerosis-linked Mutants of Superoxide Dismutase 1

Abstract: Background: Lou Gehrig's disease is accompanied by misfolding and aggregation of proteins. Results: The intramolecular reactivity of cysteines of superoxide dismutase 1 results in new disulfide bonds in unusual positions. Conclusion: Thiol/disulfide exchange reactions are altered in mutated proteins. Significance: Intramolecular reorganization of disulfides may be one of the mechanisms of protein misfolding related to neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…5) (45). Although Cys 111 is not the only residue to mediate misfolding/aggregation, it is the only Cys residue present in SOD1 from primates, and its role in ALS pathophysiology has been considered (28,45). Because of its location in the surface of the protein, Cys 111 may interact with Cys 57 or Cys 146 and reorganize the intramolecular disulfide bond (20) and would reorient the Cu 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5) (45). Although Cys 111 is not the only residue to mediate misfolding/aggregation, it is the only Cys residue present in SOD1 from primates, and its role in ALS pathophysiology has been considered (28,45). Because of its location in the surface of the protein, Cys 111 may interact with Cys 57 or Cys 146 and reorganize the intramolecular disulfide bond (20) and would reorient the Cu 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…9, which also shows how the Trx and GSH-Grx systems participate in this process. Mutation in hSOD1 dimers exposes its conserved Cys 57 -Cys 146 disulfide on the protein surface in either one or both subunits (28,29), where it is easy to be reduced by the Trx and Grx systems into dithiol form, followed by the dimer dissociation. We can also find non-conserved disulfide bond forms, as Cys 6 -Cys 111 and Cys 146 -Cys 111 in SOD1 dimers, that are in a balance because of the Trx-GSH/ Grx redox systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cystine), and the factors that control this, are less well characterized, despite the critical importance of such bonds in maintaining protein structures. Disulfide bond modification is postulated to be a key factor in determining the shelf life and activity of protein- and peptide-based medicines including antibodies and vaccines2122, in food processing and spoilage23, in amyloid and aggregate formation2425 and in some human diseases2627.…”
mentioning
confidence: 99%
“…Solsona et al found that two disease-causing mutations (G39A and A4v) alter the reactivity and disulfide bonding patterns of Sod1 using single-molecule force-clamp assays. 59 First, it was clear from single-disulfide cleavage experiments by TCep on wild-type Sod1 that the Cys57-Cys146 disulfide bond is buried, as cleavage occurred only after unfolding, generating a characteristic increase in protein length upon reduction. After unfolding, single isomerization events due to attack of Cys111 on the disulfide were observed.…”
Section: Disulfide Isomerization In Superoxide Dismutase 1 (Sod1)mentioning
confidence: 99%